Effect of bottom ash on rheological and physico-mechanical properties of high early strength self-compacting brick (HES-SCB) - Mohd Apandi, Nazirah; Ahmad Zailani, Warid Wazien; Md Zain, Mohd Raizamzamani; Beddu, Salmia; Ramli, Muhammad Zahir; Sinarta, I Nengah; Agustini, Ni Komang Ayu (UiTM Press, 2025)
This study delves into the environmentally responsible application of bottom ash (BA), a prevalent waste product from coal combustion in power plants, which constitutes 15% – 25% of total coal ash in Malaysia. The improper disposal of BA is a significant environmental hazard, with the potential to contaminate groundwater and soil, thereby affecting biodiversity and land usability. This study focuses on the novel application of BA in high early strength-self compacting brick (HESSCB), known for its rapid strength development and satisfactory flow properties, eliminating the requirement for mechanical vibration during placement. The research meticulously evaluates the substitution of BA for sand in HES-SCB, with a special focus on its influence on the fresh and physico-mechanical characteristics of the bricks. Among various mixes, the 20% BA replacement level emerged as the most significant, demonstrating a superior balance of rheological and physico-mechanical properties, thereby underscoring BA's viability as a sustainable fine aggregate substitute in HES-SCB production. This mix is designated as HES-SCB due to its distinct properties: achieving high early strength essential for rapid construction processes and exhibiting selfcompacting qualities that ensure ease of use and uniformity in application.